2021
DOI: 10.33772/jak-uho.v6i2.22229
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penggunaan Informasi Akuntansi Terhadap Kinerja Usaha, Mikro, Kecil, Dan Menengah (Umkm) Di Kota Kendari

Abstract: Penelitian ini bertujuan untuk mengetahui dan menganalisis pengaruhpenggunaan informasi akuntansi terhadap kinerja usaha mikro, kecil, dan menengah(UMKM) di Kota Kendari. Sampel pada penelitian ini menggunakan teknik purposivesampling, dan pengukuran sampel menggunakan rumus slovin, dari penentuan sampeldiperoleh 50 pengusaha. Metode pengumpulan data menggunakan kuesioner. Analisisdata menggunakan metode statistik deskriptif dan analisis regresi sederhana. Hasilpenelitian ini menunjukkan bahwa Penggunaan Infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…The better the human capital, the higher the performance of MSMEs, and vice versa. This research supports the studies by (Syahsudarmi, 2018;Tjahjadi et al, 2021), stating that human capital has a positive and significant impact on performance, and human capital has a significant positive impact on financial aspects. This researcher also supports previous studies stating that with good human capital, not only will competitive advantage be obtained, but it will also lead to an increase in business performance (Chahal & Bakshi, 2015;Hasmirati & Akuba, 2022;Muda & Rahman, 2015).…”
Section: Influence Of Financial Aspects On Business Performancesupporting
confidence: 89%
See 1 more Smart Citation
“…The better the human capital, the higher the performance of MSMEs, and vice versa. This research supports the studies by (Syahsudarmi, 2018;Tjahjadi et al, 2021), stating that human capital has a positive and significant impact on performance, and human capital has a significant positive impact on financial aspects. This researcher also supports previous studies stating that with good human capital, not only will competitive advantage be obtained, but it will also lead to an increase in business performance (Chahal & Bakshi, 2015;Hasmirati & Akuba, 2022;Muda & Rahman, 2015).…”
Section: Influence Of Financial Aspects On Business Performancesupporting
confidence: 89%
“…Research by (Pergelova & Angulo-Ruiz, 2014) also reveals that financial support seems to only have a significant impact on competitive advantage, while its role in business performance is relatively small. Research by Syahsudarmi (2018) found that financial aspects have a negative impact on business performance.…”
Section: Influence Of Financial Aspects On Business Performancementioning
confidence: 99%
“…Fenomena yang terjadi ialah masalah yang sering dihadapi oleh para pelaku usaha di Kecamatan Buleleng yakni pengelolaan keuangan serta masih ditemukan usaha yang tidak memanfaatkan informasi akuntansi, padahal bisa dijadikan landasan untuk mengambil keputusan usaha dalam upaya memperoleh keberhasilan. Dengan menggunakan informasi akuntansi secara efektif, UMKM dapat mengukur kinerja usaha, memantau arus kas, mengidentifikasi kelemahan, dan membuat keputusan yang tepat (Matahui, 2021).…”
Section: Pendahuluanunclassified
“…Usaha mikro dan menengah (UMKM) memegang peranan penting dalam perekonomian Negeri. Syahsudarmi (2018) menyatakan bahwa UMKM sanggup untuk menyediakan lapangan kerja, meningkatkan penerimaan negeri yang berasal dari pajak UMKM, dan menaikan Produk Domestik Bruto (PDB). Sehingga UMKM dinyatakan mempunyai akitifitas yang memiliki kontribusi yang prositif kepada pertumbuhan ekonomi di Indonesia.…”
Section: Pendahuluanunclassified